Unraveling the Difference between Invertases and Fructan Exohydrolases: A Single Amino Acid (Asp-239) Substitution Transforms Arabidopsis Cell Wall Invertase1 into a Fructan 1-Exohydrolase - Le Roy, Katrien (American Society of Plant Biologists, 2007)
Plant cell wall invertases and fructan exohydrolases (FEHs) are very closely related enzymes at the molecular and structural level (family 32 of glycoside hydrolases), but they are functionally different and are believed to fulfill distinct roles in plants. Invertases preferentially hydrolyze the glucose (Glc)-fructose (Fru) linkage in sucrose (Suc), whereas plant FEHs have no invertase activity and only split terminal Fru-Fru linkages in fructans. Recently, the three-dimensional structures of Arabidopsis (Arabidopsis thaliana) cell wall Invertase1 (AtcwINV1) and chicory (Cichorium intybus) 1-FEH IIa were resolved. Until now, it remained unknown which amino acid residues determine whether Suc or fructan is used as a donor substrate in the hydrolysis reaction of the glycosidic bond. In this article, we present site-directed mutagenesis-based data on AtcwINV1 showing that the aspartate (Asp)-239 residue fulfills an important role in both binding and hydrolysis of Suc. Moreover, it was found that the presence of a hydrophobic zone at the rim of the active site is important for optimal and stable binding of Suc. Surprisingly, a D239A mutant acted as a 1-FEH, preferentially degrading 1-kestose, indicating that plant FEHs lacking invertase activity could have evolved from a cell wall invertase-type ancestor by a few mutational changes. In general, family 32 and 68 enzymes containing an Asp-239 functional homolog have Suc as a preferential substrate, whereas enzymes lacking this homolog use fructans as a donor substrate. The presence or absence of such an Asp-239 homolog is proposed as a reliable determinant to discriminate between real invertases and defective invertases/FEHs.